(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2021)
The article describes the socio-cultural processes and public views of the Poltava province society formed under the influence of the First World War. The phenomena aroused during the war of 1914-1918 are examined, their influence on fundamental changes in the socio-political, economic and cultural life is investigated. It is noted that at the end of the 19th – beginning of the 20th centuries the public consciousness of the population of Poltava region represented a complex system of ideas, views, moods and was formed under the influence of cultural tradition and modernization processes. It is demonstrated that the cultural life of the Poltava region at the beginning of the twentieth century was characterized by a wide range of diverse practices both folk-ritual and urban-modernistic ones. It is proved that in wartime conditions a mass culture was formed; its influence spread over a large part of society.